Notes on Irrigated Agriculture on the Peruvian Coast - Golte, Jürgen (1980)
Each way of producing has very specific preconditions and social consequences. The development of the productive forces, in the various stages of history and in different regions, shows this very clearly. Starting from the effort to understand the specificity of European economic and social development compared to Asian societies, Marx developed the concept of an Asian mode of production which would have prevented private ownership of the means of production from fully developing in Eastern societies with its later implications. This course of history would have been determined first of all by differences in the forms of agricultural production.